Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 116 species occurrences available in GBIF matching the query: { "and" : [ "Year 1967-2017", "Geometry POLYGON((-5 50,-5 60,10 60,10 50,-5 50))", "HasCoordinate is true", "TaxonKey is Tubulipora liliacea (Pallas, 1766)", "HasGeospatialIssue is false" ] } The dataset includes 116 records from 13 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001004-170817152713382/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences